'Are we downhearted? NO!': representing war damage and destruction following bombardment on the First World War 'home front'. Issue 4 (2nd October 2021) - Reeve, Michael
ABSTRACT: Using four bombarded coastal locations in north-east England as case studies, this article explores the phenomenon of bomb damage imagery and its use in propaganda and commemorative processes during the First World War. Through an analysis of postcards, souvenirs and other aspects of wartime material culture, this article posits that depictions of bomb-damaged and destroyed buildings – both monumental and vernacular – were central to local and national efforts to memorialise and make sense of the passing of enemy actions on the home front, during a period when civilians were increasingly seen as legitimate targets.